Innate defense mechanisms against Nosema ceranae in hygienic honey bee (Apis mellifera) colonies - M. Sydney Miller; Dawn Boncristiani; Jay Evans; P. Alexander Burnham; Cailin Barrett; Kaira Wagoner; Samantha A. Alger (PLoS ONE, 2026)
The honey bee colony ( Apis mellifera ) acts as a superorganism, with a dual immune system that operates at the individual and social level. However, the linkages between immune mechanisms across the two levels remain poorly understood, despite the relevance for developing effective breeding strategies to improve honey bee disease resistance. Hygienic behavior involving the removal of unhealthy brood is a key component of honey bee social immunity and is highly effective at limiting parasites and pathogens in the colony. While this form of hygienic behavior can reduce brood diseases, parasites infecting adult bees primarily, such as Nosema ceranae, are not directly impacted by the behavior. However, when using the Unhealthy Brood Odor (UBeeO) assay to quantify hygienic behavior performance, hygienic colonies have been shown to maintain lower Nosema spp . loads over time and overall compared to non-hygienic colonies. To investigate the mechanisms driving reduced Nosema spp . in hygienic colonies, we conducted a series of field and lab experiments to test the innate immune performance of individual bees. We evaluated several factors across hygienic and non-hygienic bees including (1) differences in N. ceranae infection levels, (2) survival probability, (3) Vitellogenin and Hymenoptaecin gene expression, and (4) amount of N. ceranae inoculant consumed. We found that hygienic bees consumed less of the inoculant, exhibited upregulated Vitellogenin gene expression at peak N. ceranae infection, showed a positive relationship between Hymenoptaecin gene expression and N. ceranae infection levels, and had greater survivability when infected with N. ceranae , compared to non-hygienic bees. Here, we present new findings that link colony hygienic behavior performance to individual-level resistance and tolerance mechanisms in response to N. ceranae , suggesting broader implications for the success of selective breeding programs targeting hygienic traits.